2022
DOI: 10.3390/membranes12030310
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular-Weight Lignin Recovery with Nanofiltration in the Kraft Pulping Process

Abstract: Kraft lignin is an underutilized resource from the pulp and paper industry with the potential of being a key raw material for renewable fuels and chemicals. The separation of high-molecular-weight lignin from black liquor by ultrafiltration has been widely investigated, while the permeate containing low-molecular-weight lignin has received little attention. Nanofiltration can concentrate the low-molecular-weight lignin. This work, therefore, evaluates nanofiltration for the separation and concentration of low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The separation of high-molecular-weight lignin from black liquor has been achieved by UF, but the presence of low-molecular-weight lignin in the UF permeate has been little studied. The results of nanofiltration of a UF permeate with polymeric membranes have demonstrated that lignin can be recovered with a maximum recovery of 94% at a TMP of 35 bar . Furthermore, separate studies examined the effects of activated carbon nanoparticles (AC) and carbon nanotubes (CNTs) on polymeric membranes, and the results indicated lignin removal of 80–98% from black liquor with a 90% water recovery due to membrane modification. , Overall, NF treatment technology is not yet cost-effective for paper recycling processes, due to the energy consumption and pretreatment unit required …”
Section: Physical and Chemical-based Treatmentmentioning
confidence: 99%
“…The separation of high-molecular-weight lignin from black liquor has been achieved by UF, but the presence of low-molecular-weight lignin in the UF permeate has been little studied. The results of nanofiltration of a UF permeate with polymeric membranes have demonstrated that lignin can be recovered with a maximum recovery of 94% at a TMP of 35 bar . Furthermore, separate studies examined the effects of activated carbon nanoparticles (AC) and carbon nanotubes (CNTs) on polymeric membranes, and the results indicated lignin removal of 80–98% from black liquor with a 90% water recovery due to membrane modification. , Overall, NF treatment technology is not yet cost-effective for paper recycling processes, due to the energy consumption and pretreatment unit required …”
Section: Physical and Chemical-based Treatmentmentioning
confidence: 99%
“…The commonly used lignin separation methods include acid precipitation and membrane separation methods [8]. The acid precipitation method is characterized by a simple process and a low cost, but it requires a quantity of acid, which easily causes secondary pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Their subsequent separation can be accomplished using membrane processes [2]; however, these wood constituents can potentially foul the membrane systems employed in the fractionation and concentration of the desired components. Studies on pressure-driven membrane filtration have been conducted using process waters from thermomechanical pulp mills [3][4][5], Kraft black liquor [6][7][8], and spent sulfite liquor [9][10][11]. These studies highlight the complex interactions of wood components, necessitating advanced techniques for monitoring their fouling behavior rather than relying solely on changes in permeate flux and transmembrane pressure (TMP).…”
Section: Introductionmentioning
confidence: 99%